Social relations between humans and animals: A challenge for the total defence? (Sociologisk Forskning, 2023)
The war in Ukraine has had an extensive impact upon societies not directly involved in the military fighting. Traditional and social media has been filled with references to the war and discussions concerning how individuals as well as society as a whole would cope if war were to erupt in Sweden. In this context, an often overlooked issue is the relationship between humans and animals. This article discusses challenges to the total defence system, brought on by the norms of the 2020s, concerning the social relationship between humans and animals. It presents a number of areas wherein the relation between humans and animals is likely to raise questions and invoke conflict with existing regulations of the total defence: views of security, laws and regulations for wartime and crisis situations, and the development of social relations between humans and animals. Finally, some ideas are presented regarding how a total defence including animals could be materialized, and which changes such ideas would pose to the present total defence.
Keywords: defence policy; total defence; animals; human–animal studies; Ukraine